1995
DOI: 10.1038/bjc.1995.54
|View full text |Cite
|
Sign up to set email alerts
|

The Arg-Gly-Asp-containing peptide, rhodostomin, inhibits in vitro cell adhesion to extracellular matrices and platelet aggregation caused by saos-2 human osteosarcoma cells

Abstract: Sumary Saos-2 cells, derived from a primary human osteosarcoma, caused dose-dependent platelet aggregation in heparinised human platelet-rich plasma. Saos-2 tumour cell-induced platelet aggregation (TCIPA) was completely inhibited by hirudin but unaffected by apyrase. The cell suspension shortened the plasma recalcification times of normal, factor VIII-deficient and factor IX-deficient human plasmas in a dosedependent manner. However, the cell suspension did not affect the recalcification time of factor VII-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…[16][17][18] Pretreatment of either tumor cells or platelets with an antibody or peptide that neutralizes vWF or blocks vWF-capable receptors (eg integrins GPIIb/ IIIa and GPIb-present on numerous tumor cell lines) has been shown to inhibit tumor cell-platelet interaction in vitro for colon carcinoma, Walker 256 carcinosarcoma, melanoma and osteosarcoma cell lines (including SAOS2). 19,[44][45][46][47][48][49][50][51][52] Notably, treatment with monoclonal anti-vWF antibody significantly decreased tumor cell metastases in vivo for colon, Lewis bladder and melanoma carcinoma cell 53 suggested that this tumor cell-platelet mechanism may be partially responsible for the common metastasis of osteosarcoma to the lung. In support of this, the osteosarcoma cell lines MG63, HOS, U2-OS, TE-85 and SAOS2 have been shown to induce platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Pretreatment of either tumor cells or platelets with an antibody or peptide that neutralizes vWF or blocks vWF-capable receptors (eg integrins GPIIb/ IIIa and GPIb-present on numerous tumor cell lines) has been shown to inhibit tumor cell-platelet interaction in vitro for colon carcinoma, Walker 256 carcinosarcoma, melanoma and osteosarcoma cell lines (including SAOS2). 19,[44][45][46][47][48][49][50][51][52] Notably, treatment with monoclonal anti-vWF antibody significantly decreased tumor cell metastases in vivo for colon, Lewis bladder and melanoma carcinoma cell 53 suggested that this tumor cell-platelet mechanism may be partially responsible for the common metastasis of osteosarcoma to the lung. In support of this, the osteosarcoma cell lines MG63, HOS, U2-OS, TE-85 and SAOS2 have been shown to induce platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, the osteosarcoma cell lines MG63, HOS, U2-OS, TE-85 and SAOS2 have been shown to induce platelet aggregation. 46,[53][54][55] The vWF produced by SAOS2 may contribute to its ability to aggregate platelets. vWF expression by osteosarcoma tumor cells may contribute to tumor cell-platelet aggregation as well as tumor-subendothelium adhesion, increasing the likelihood of successful blood-borne metastasis to the lung.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation may be related to the functional adhesion motifs of SAA. According to previous reports, some proteins containing the peptide Tyr-IIe-GlySer-Arg (YIGSR) and/or Arg-Gly-Asp (RGD) demonstrated inhibition activities in tumor cell invasion and metastasis, such as the multimeric YIGSR-containing peptide (Ac-Y16), and RGD-containing peptide (rhodostomin) (29)(30)(31). Both functional YIGSR-like and RGD-like motifs also present in the SAA protein (22).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin can affect the expression or distribution of integrins on the tumor cell surface (15)(16)(17). The Arg-Gly-Asp (RGD)-containing snake venom peptide and synthetic peptides can block thrombin-mediated tumor cell adhesion (15,18). However, the mechanism by which thrombin activates integrins has not yet been clearly described.…”
Section: Introductionmentioning
confidence: 99%